The Decibel Levels of TV and the Elusive Social Will - K. R., Subramanian (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2018)
There is no dearth of media TV channels for the news of happenings around us. Through the din and noise of the TV commercials and the intermittent serials, we get news trickling down, often not any events or historic moments but the political cog mire of parliamentary or legislative arguments and the media interviews trying to brow beat any politician. Or the so called discussion in which the decibel levels of shouting matches take place! ; The media has a pet phrase ‘the public wants to know’, but often it may the least of interest for common people to know. The people at large would like to know if there is a fall in vegetable or grocery prices or improvement in industrial production or employment. But people often have to content with the Political or Advertisement Commercial noise! What people want to know is when this will stop and there will be realistic report of news. It is a nightmare experience for the TV and media viewers to contend with rising noise level often leading to switching off. Social will is absolutely necessary. This article is to find out if there is any solution for this problem!